Beyond Objectivity in Audio Description: New Practices and Perspectives - Schaeffer-Lacroix, Eva; Reviers, Nina; Di Giovanni , Elena (Journal of Audiovisual Translation, 2023)
For many years, objectivity was considered a key norm of quality in audio description (AD), and it still features prominently in many AD guidelines. The primary motivation behind the concept is a recognition of users' autonomy in forming a mental image of the audiovisual content independently. Research has offered many alternative views on the issue that conceptualise the idea of objectivity/subjectivity as a continuum, emphasizing that different approaches can be appropriate depending on the given context of situation, giving rise to different AD styles that cater for a range of aesthetic preferences. Against this background, various cultural domains are experimenting with alternative approaches, challenging established AD practices and the assumptions it is built on. The articles included in this special issue all explore the various ways in which AD user needs can be met and illustrate the dynamic views that exist on objectivity, addressing key questions related to the operationalisation of objectivity, the challenge of interpretation for AD, the exploration of emerging subjective styles, and the concept of aesthetics of or in access.